2016
DOI: 10.1074/jbc.m115.711812
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Injury Diminishes Opioid Analgesia through Lysine Methyltransferase-mediated Transcriptional Repression of μ-Opioid Receptors in Primary Sensory Neurons

Abstract: The -opioid receptor (MOR, encoded by Oprm1) agonists are the mainstay analgesics for treating moderate to severe pain. Nerve injury causes down-regulation of MORs in the dorsal root ganglion (DRG) and diminishes the opioid effect on neuropathic pain. However, the epigenetic mechanisms underlying the diminished MOR expression caused by nerve injury are not clear. G9a (encoded by Ehmt2), a histone 3 at lysine 9 methyltransferase, is a key chromatin regulator responsible for gene silencing. In this study, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
79
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 49 publications
12
79
1
Order By: Relevance
“…Given that G9a is co-localized with Kcna2 in the DRG neurons, it is very likely that G9a participates in the mechanisms underlying neuropathic pain development by downregulating Kcna2 in the axotomized DRG. However, other potential mechanisms of G9a involvement in neuropathic pain cannot be ruled out, because G9a regulates the expression of other genes in the axotomized DRG33.…”
Section: Discussionmentioning
confidence: 99%
“…Given that G9a is co-localized with Kcna2 in the DRG neurons, it is very likely that G9a participates in the mechanisms underlying neuropathic pain development by downregulating Kcna2 in the axotomized DRG. However, other potential mechanisms of G9a involvement in neuropathic pain cannot be ruled out, because G9a regulates the expression of other genes in the axotomized DRG33.…”
Section: Discussionmentioning
confidence: 99%
“…SUV39H1 likely contributes to nerve injury-induced nociceptive hypersensitivity through epigenetic silencing of MOR in the injured DRG. Nerve injury-induced DRG MOR downregulation is also restored by the inhibition of DRG histone deacetylase or G9a 38;43;44 , suggesting multiple epigenetic mechanisms by which the MOR gene is silenced in the injured DRG after peripheral nerve injury. Compensation by other mechanisms may not occur, as blocking each mechanism can restore MOR expression in the injured DRG.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in response to nerve injury (spinal nerve ligation), the expression of both μ-receptor mRNA and mu receptor-related proteins decreased [56]. More recently, a group has managed to characterize and describe these changes [57]. This study observed that down-regulation of mu opioid receptors occurs in the dorsal root ganglion, but not the spinal cord [57].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%
“…More recently, a group has managed to characterize and describe these changes [57]. This study observed that down-regulation of mu opioid receptors occurs in the dorsal root ganglion, but not the spinal cord [57]. The authors of this study also used mice with a knockout Ehmt2 (a histone methyltransferase) and observed that the knockout mice did not experience nerve-injury related resistance to opioid therapy [57].…”
Section: How Do Pharmacological Interventions Take Advantage Of Pamentioning
confidence: 99%